Trichrysis baratzsensis sp. nov. (Hymenoptera: Chrysididae) from Sardinia - Strumia, Franco (Zootaxa, 2009)
Trichrysis baratzsensis sp. nov., from Lago Baratz (Sassari province, Sardinia), is described and compared with all other Palaearctic congeners. A key for the identification of Mediterranean Trichrysis species is also provided.